Chile 2010: Political Disaffection and its Impact on the Conventional and non-Conventional Political Participation - Disi Pavlic, Rodolfo; Mardones Arévalo, Roberto (Revista del CLAD Reforma y Democracia, 2019)
The decrease of political participation in Chile since the early 90s lead to a discussion about political disaffection in the beginning of the new century. To what extent does political disaffection affect the decrease in political participation? Previous studies on this subject have been theoretical and descriptive and have only linked disaffection to the electoral participation. This study argues that higher levels of political disaffection are associated to less conventional and unconventional political participation. To demonstrate this the Auditoría a la Democracia (2010) survey is used to perform statistical analyzes of political disaffection on different types of political behavior. Results show that political disaffection is a compound and internally coherent concept, consisting of attitudes of distrust towards political actors and institutions, no interest in politics, internal and external inefficacy, and democracy dissatisfaction. Regression analyses, using participation rates as a dependent variable, also conclude that disaffection has a negative effect on both dimensions of political participation.